2022
DOI: 10.3389/fnagi.2022.996234
|View full text |Cite
|
Sign up to set email alerts
|

Effect of human probiotics on memory, psychological and biological measures in elderly: A study protocol of bi-center, double-blind, randomized, placebo-controlled clinical trial (CleverAge Biota)

Abstract: BackgroundGut microbiota may influence brain functions. Therefore, we prepared a study protocol for a double-blind, crossover, randomized clinical trial to determine the complex effects of human probiotics on memory, psychological, and biological measures in the elderly.MethodsWe selected eligible participants using an effective electronic questionnaire containing the inclusion and exclusion criteria and a brief electronic cognitive test. One-third of the respondents with the worst cognitive scores on the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…The detailed protocol for this study can be found in our previous paper ( Bartos et al, 2022 ). Here we briefly describe participants´ characteristics and procedures.…”
Section: Participants and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed protocol for this study can be found in our previous paper ( Bartos et al, 2022 ). Here we briefly describe participants´ characteristics and procedures.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Due to the controversies within this evolving area of study, we decided to design a randomized clinical trial with a cross-over design ( Bartos et al, 2022 ). Studies focusing on cognitively normal or mildly affected older adults are scarce ( Tahmasbi et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several randomized, double-blind, placebo-controlled clinical trials have evaluated the efficacy of probiotics in patients with MCI with mixed results [5,10,122]. In addition, the safety and feasibility of oral fecal microbiota transplant is being evaluated [23].…”
Section: Bacterial Dysbiosismentioning
confidence: 99%
“…In this situation, whether probiotic adjuvant therapy may improve the regulation of neuroinflammation is a crucial consideration for future investigations. The potential cognitive benefits of probiotic adjuvant therapy are worth looking forward to 174 . A recent clinical cross‐sectional study demonstrated a correlation between alterations in the gut microbiome composition of patients with AD and β‐amyloid and tau pathological biomarkers, suggesting that changes in the gut microbiome may occur early in the disease process and have an association with cognitive impairment.…”
Section: Microbiota‐based Implications For Therapeutic Interventionsmentioning
confidence: 99%
“…The potential cognitive benefits of probiotic adjuvant therapy are worth looking forward to. 174 A recent clinical cross‐sectional study demonstrated a correlation between alterations in the gut microbiome composition of patients with AD and β‐amyloid and tau pathological biomarkers, suggesting that changes in the gut microbiome may occur early in the disease process and have an association with cognitive impairment. Probiotics may mitigate COVID‐19‐induced cognitive impairments through the regulation of neuroinflammation, modulation of the gut microbiota, and gut homeostasis.…”
Section: Microbiota‐based Implications For Therapeutic Interventionsmentioning
confidence: 99%